2001
DOI: 10.1007/s004240100008
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and proliferation in the testes of the brown hare ( Lepus europaeus ) under the influence of photoperiod

Abstract: Brown hare is a seasonal breeding mammal and under the influence of photoperiod the spermatogenesis ceases during autumn months - most markedly in September and October. Testis samples from 34 animals, sacrificed between July and December were fixed in Bouin solution, embedded in paraffin, subjected to immunohistochemistry and analysed by light microscopy. TUNEL (terminal deoxynucleotidyl transferase-mediated d'UTP nick end labeling) method was applied to detect apoptosis, anti PCNA (proliferating cell nucleol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Germ cell proliferation has been observed in regressed testis of animals exposed to short photoperiod, as the brown hare (Strbenc & Bavdek, 2001) and the hamster (Schlatt & Weinbauer, 1994). It has been suggested that the rate of celldivision may decrease in the testis during regression, indirectly contributing to seasonal atrophy (Young et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell proliferation has been observed in regressed testis of animals exposed to short photoperiod, as the brown hare (Strbenc & Bavdek, 2001) and the hamster (Schlatt & Weinbauer, 1994). It has been suggested that the rate of celldivision may decrease in the testis during regression, indirectly contributing to seasonal atrophy (Young et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…). In these animals, there is a significant reduction in testicular volume during the non‐breeding season, accompanied by a strong increase in cell apoptosis in the seminiferous epithelium (Strbenc and Bavdek ; Young et al. ; Jenkins et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells, spermatogonia and primary spermatocytes can be observed with the tubules. Leydig cells resemble fibroblasts (Strbenc & Bavdek, 2001). In short photoperiods (less than 12–12.5 h of light) atrophy in the testes occurs, resulting in a decrease in spermatogenesis and steroid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…, 2005). It was found that, while there was an increase in apoptosis in the seminiferous tubules secondary to seasonal and photoperiodic changes, proliferation activity was retained in cells (Strbenc & Bavdek, 2001; Sato et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%